IMPLEMENTATION OF NAZHARIYYAH AL-MAQÂSHID IBNU 'ASYUR IN THE PROHIBITION OF WOMEN PNS BECOME WIFES OF POLYGAMIC HUSBANDS - agus trimulyo (Hukum Keluarga Islam, 2024)
Studies on maqahid sharia continue to find relevance in addressing various socio-religious realities. The maqashid sharia developed by Ibn Asyur had a significant influence on the scientific independence of maqashid sharia from Ushul Fiqh. Ibn Asyur's Maqashid Syariah can be an offer to become a measuring tool for legal ijtihad in resolving socio-religious cases, as well as being a tool for evaluating various policies related to Muslims, including problems related to polygamy. The Indonesian government generally allows men and women to engage in polygamy with various terms and conditions. Via PP. NO 45 of 1990, the Government prohibits female civil servants from becoming wives of polygamous husbands. This regulation is still the subject of polemics and discussions. This research uses descriptive analysis by examining various literature related to the research object. This research discusses the profile of Ibn Asyur, maqashid sharia as a result of Ibn Asyur's study and discusses polygamy in relation to various government regulations. This qualitative research found that through the tarjih process, these regulations were in accordance with Ibn Asyur's maqashid sharia.